The Economic Burden on Private Hospitals in Treating ICU Vs Non-ICU Patients: Investigating The Financial Gap Between Indonesian Case Base Groups (INA-CBG) Rates and Hospital Billing - Halim, Ida Juita; Manggala, Sidharta Kusuma (Writing Center IMERI FMUI, 2024)
Objectives: Indonesia’s healthcare financing relies on a bundled payment system, the Indonesian Case Base Groups (INA-CBG) rates, whereas private hospitals calculate costs using Activity-Based Costing (ABC). This difference can lead to significant financial gaps, especially in ICU and non-ICU care. Methods: A random sample of 93 ICU and non-ICU patients from a private hospital in Bekasi, West Java, was analyzed. We compared the INA-CBG rates and hospital billing for ICU and non-ICU care by considering comorbidities, hospital length of stay (LOS), and mortality rates. Results: The average LOS was longer for ICU patients (6.78 days) than non-ICU (4.98 days). The ICU mortality rate was 20%, while non-ICU was 2.33%. Globally, ICU LOS averages 5-7 days, with a 30% mortality rate. INA-CBG covered only 41.89% of costs for non-ICU patients and 57.14% for ICU patients. Conclusion: This study demonstrates the significant financial strain created by the discrepancy between the INA-CBG claims and the actual costs particularly for private hospitals handling patients with high severity.